Alexander Technique classes for tertiary music students: Student and teacher evaluations of pre- and post-test audiovisual recordings. (May 2020) - Davies, Janet
Tertiary music students show patterns of playing-related musculoskeletal disorders (PRMDs) similar to professionals, indicating the need for effective education in management and prevention during student years. When problems occur, music students are most likely to seek advice from their instrumental teachers; therefore, it is important for teachers to be involved in ensuring education programs are relevant to the occupational and artistic needs of both student and professional musicians. Musicians have previously reported improvements in outcomes associated with PRMDs and performance quality following Alexander Technique (AT) classes. In this study, 12 university music students and eight of their teachers evaluated video-recordings filmed before and after a semester of weekly, purpose-designed AT classes. Positive changes were observed in muscle tension, posture, tonal resonance, breathing, instrumental technique, and movement quality. Noted improvements were consistent with student participants' subjective experiences, reported previously from questionnaire data. The results suggest that AT training at the instrument may have a direct positive impact on key factors associated with PRMDs as well as playing quality. Use of video assessments as a component of controlled, mixed-method studies with larger populations is recommended to establish the potential value of AT for inclusion in music training.